COVID‐19 and maternal and child food and nutrition insecurity: a complex syndemic - Pérez‐Escamilla, Rafael; Cunningham, Kenda; Moran, Victoria Hall (Maternal and child nutrition, 2020)
Globally, the COVID‐19 pandemic has already led to major increases in unemployment and is expected to lead to unprecedented increases in poverty and food and nutrition insecurity, as well as poor health outcomes. Families where young children, youth, pregnant and lactating women live need to be protected against the ongoing protracted pandemic and the aftershocks that are very likely to follow for years to come. The future wellbeing of the vast majority of the world now depends on reconfiguring the current ineffective food, nutrition, health, and social protection systems to ensure food and nutrition security for all. Because food, nutrition, health, and socio‐economic outcomes are intimately inter‐linked, it is essential that we find out how to effectively address the need to reconfigure and to provide better intersecoral coordination among global and local food, health care, and social protection systems taking equity and sutainability principles into account. Implementation science research informed by complex adaptive sytems frameworks will be needed to fill in the major knowledge gaps. Not doing so will not only put the development of individuals at further risk, but also negatively impact on the development potential of entire nations and ultimately our planet.